Knowledge and lifestyle practices associated with non-communicable diseases risk factors among undergraduate students, Thiruvananthapuram, India: a mixed method study - Bijumone, Sandhya; A., Chitra Grace (International Journal Of Community Medicine And Public Health, 2024)
Background: Behaviors established in youth especially in college, have lifelong implications on themselves and their close family members. We intended to assess the knowledge of non-communicable diseases (NCDs) risk factors and associated lifestyle practices among undergraduate students. Methods: We conducted a cross-sectional concurrent mixed method study among undergraduate students (n=486) aged 18-21 years, Kerala, India. A self-administered structured questionnaire was used to collect data. In-depth interviews of five students were conducted from each college. Physical measurements including height and weight of the students were measured and reported to the participants. Data was collected from January to March 2019. Results: Forty-four percent (n=200) participants’ fathers were laborers or semi-skilled workers. Only 42.8% (n=208) of students had body mass index (BMI) within normal range. Nearly three fifth of students (58%, n=282) had poor knowledge of NCDs and proportion of students with knowledge of balanced breakfast was 11% (n=53). Regarding lifestyle practices, daily fruit intake was low (10%, n=45) and participants consuming vegetables daily was less than 40% (n=191). Lack of infrastructure supporting physical activities and healthy food choices at home and outside are some reasons mentioned by participants for sedentary lifestyle and unhealthy dietary practices. Parental involvement played an important role in practicing healthy dietary practices and performing physical activity for leisure. Conclusions: The knowledge and practices of undergraduate students regarding primary prevention of NCDs was poor. Community level action with involvement of parents will be helpful in the primary prevention of NCDs.